Nanostructure investigation of Eu3+-containing porous silica glasses: Influence of pore size and sintering conditions. Issue 12 (15th August 2018) - de Pablos-Martín, A.; Oberleiter, B.; Thieme, C.; Rainer, T.; Höche, T.
Abstract: Porous silica glasses of different porous sizes are used as hosts for Eu 3+ -ions from a Eu(NO3 )3 solution. The glasses were subjected to a sintering process in which the porous microstructure collapses. This work is dedicated to the study of the microstructure of sintered glasses containing Eu 3+ ions, through (scanning) transmission electron microscopy ((S)TEM), energy-dispersive X-ray spectroscopy (EDXS), and X-ray diffraction (XRD). The microstructure achieved is strongly dependent on the pore size, heating rate, and sintering temperature. Eu 3+ ions are localized in particles growing in the pores during the sintering.